A survey of audience reception of atọ́ka, a yorùbá photoplay magazine (2019)
Atọ́ka is a Yorubá photodrama magazine produced in Lagos, Southwest Nigeria from 1967-1991. Published by West African Book Publishers (WABP) and printed by their sister company, Academy Press, Atọ́ ka was a bi-monthly magazine which, while it lasted, hit the stands fortnightly. Extensive works have been done on Yorubá drama by several scholars. While some looked at specific theater companies, some studied the selected plays of particular companies, and some others examined the production of certain organizations at a particular phase. Despite these myriad of works, some other production media, particularly the stage, celluloid film, and home video film, have gained the attention of researchers extensively but photoplay in particular, and radio, television, and the phonograph-disc have not been so lucky. Apart from some works (Ogúndeji 1981, Aróhunmọ́ lasẹ ̣ 1982, Adeó ye 1984, Bọ́láji ́ 1985, Adéléke 1995, and Akangbé 2014) that referred to and passed comments on Yorubá photoplay, no one has carried out a seminal study on the history, production, and content of Atọ́ka photoplay magazine. None of the aforementioned endeavors focused on the audience reception of Atọ́ka photoplay magazine. By implication, there are very scanty works on the photoplay genre and virtually none on audience reception of Yorubá photoplay magazine. It is this yawning gap that this study intends to fill by studying the peculiarities of the readers of Atọ́ka photoplay magazine. This paper is divided into nine parts, namely: Abstract, Introduction, Overview of Yorubá photoplay magazine, eception theory, Methodology, Data analysis, Discussion of findings, Conclusion, and Recommendations.